OP0028 Association of Differential Synovial Expression Patterns in Early Osteoarthritis with Pain and Progression of Joint Damage. (15th July 2016) - Blom, A.; van den Bosch, M.; Cats, H.; van den Hoogen, F.; Lafeber, F.; van den Berg, W.; van Lent, P.; van der Kraan, P.
Abstract : Background: The cause for chronic pain in OA is largely unknown. Over 50% of osteoarthritis (OA) patients show synovial inflammation, even at early stages of the disease. However, if and how this synovial activation contributes to joint pathology and pain, is not known. Objectives: To identify pathways that predict progression of cartilage damage and osteophyte (OP) formation in OA. In addition, we identified association between gene expression and pain in a cross-sectional approach. Methods: From 25 patients with knee OA that entered the CHECK Cohort study (Cohort Hip and Cohort Knee) synovial biopsies were collected at baseline. CHECK is a prospective 10-year follow-up study on patients with early osteoarthritis-related complaints initiated by the Dutch Arthritis Foundation. Progression over 5 years was determined radiographically based on change of joint space width (JSW) and OP size in these radiographs. Pain was assessed at baseline by the WOMAC pain questionnaire. Synovial samples from baseline were studied using histology and microarray (affymetrix U133-plus-2.0), and Functional Annotation Clustering (FAC). Results: We identified patients that were marked progressors or non-progressors, either based on JSW (respectively n=13 vs n=8) or OP size (respectively n=10 vs n=11) at these time points. Among the genes that were differentially expressed by OP progressors were MMP1, 2, 3, 9 and -14, whereas in JSW-progressors only MMP1 was differentially expressed. In the group of JSW-progressors, macrophage markers like CD14, S100A8, S100A9, MHC class II genes, and CXCR2 were positively associated with progression. This indicates that expression of these factors predict progression of cartilage damage in OA patients. The OP-progressors showed an increase of most of these markers, but to a far lesser extent. Using FAC we identified inflammatory response, macrophage differentiation, blood vessel formation, ossification and cell migration to be enriched in JSW-progressors. Blood vessel formation, wound healing, ossification and cell proliferation were enriched in OP-progressors. Histologically, in the JSW-progressors the lining layer was thicker and the cellularity was higher in the sublining compared to non-progressors, and compared to OP progressors. Both JSW-progressors and osteophyte-progressors showed increased vascularisation compared to non-progressors. At baseline, FAC analysis pointed out that dendrite formation (p=0.036) response to heatshock/stress (p=0.015) and voltage gated ion transport (p=0.013) were annotation clusters that were related to pain. Surprisingly, no positive relation was found between inflammatory mediators and pain. In line with this, no relation between histological inflammation or lining thickness and pain was found. Conclusions: We found evidence for a difference in underlying processes in the synovium regarding progression of cartilage damage and progression of osteophyte formation. The presence of macrophages, especially in the lining layer, is associated with progression of cartilage damage, whereas synovial expression of MMPs correlated to progression of osteophyte formation. Pain was associated with several nerve fiber related processes. Disclosure of Interest: None declared